Problematika Kajian Tafsir di Perguruan Tinggi Islam dan Masyarakat Kalimantan Selatan - Wardani Wardani (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2020)
This article is intended to examine the development of published works on the interpretation of the Qur’ān in South Kalimantan in the 2000s, by comparing the works written by intellectuals in Islamic university (in the case of Antasari State Islamic University, Banjarmasin) and beyond. By applying the continuity-change and challenge-response approaches, this article finds that the two types of exegetical works show that the authors' interpretation is limited to theory, not yet in an effort to produce original interpretive works. In general, most of the exegetical works written by intellectuals in Islamic university are intended to meet the formal requirements of education, such as achieving degrees and preparing lecture handbooks. Meanwhile, the works of Muslim intellectuals beyond the university appear to be more responsive to many issues, such as issues of ritual, science, and magic. In terms of originality, both exegeses work mostly originate from traditional sources, while the former applies a thematic approach (mawḍū‘ī) as a tool for modern interpretation and the latter applies an analytical approach (taḥlīlī) for a conventional one.